Green HRM, Motivation, and Work Engagement Influencing Airline Management Performance: A Systematic Literature Review - Devi Marlita; Yulianti Keke; Abdullah Ade Suryobuwono; Otto Sugiharto Prakoso; Muhammad Tohir; Primadi Candra Susanto (Goodwood Publishing, 2026)
Purpose: This study conducts a systematic literature review on the relationships among Green Recruitment, Green Training, motivation, Work Engagement, and airline management performance in the Indonesian aviation context using a Green Human Resource Management (HRM) perspective. Methodology: This study employed a Systematic Literature Review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature from Scopus, Web of Science, Emerald, Springer, and Google Scholar published between 2020 and 2025 was screened using predefined criteria. A total of 42 relevant peer-reviewed articles were selected and analyzed using thematic and comparative synthesis. Results: Prior studies suggest that Green Recruitment, Green Training, and employee motivation are positively associated with Work Engagement and airline management performance. Work Engagement consistently appears to be an important mediating mechanism linking green HRM practices and management performance. The findings further indicate that environmentally oriented HRM practices contribute to organizational sustainability, operational effectiveness, and employee commitment in the aviation industry. Conclusions: Green Recruitment, Green Training, and motivation improve Work Engagement and airline management performance. Work Engagement also acts as a key mediating variable. Limitations: This study’s limitations lie in its literature review-based nature, thus requiring supporting primary data from existing airlines in Indonesia. Contributions: This study contributes a framework for airline company managers to understand how green recruitment, green training, and motivation can improve performance through work-engagement.